Discussing Reframing Strategies for Learning Financial Literacy in Children - Weni Tria Anugrah Putri; Muhammad Heryudanta (Tarbiyah Departement collaboration with AMCA, 2021)
Financial literacy is not a study that is rarely discussed. Not a few people who managed to master it. In fact, in several scientific sources, there are also people who only know about the concept of financial literacy but do not understand and apply it. This study aims to discuss the reframing strategy that aims to collect various kinds of positive perceptions about financial literacy. In addition, this study also discusses reframing strategies in children for learning financial literacy. This study focuses on the stages of the reframing strategy based on studies conducted by Cormier, namely rationalization, identification of perceptions, unraveling the role of selected perceptual features; identification of alternative perceptions; modification of perceptions in problem situations, homework and follow-up. In this series of stages, the formation of perceptions according to Weber's theory of perception is also studied. With this study, it is hoped that parents will have two social actions, namely instrument rationality and value-oriented rationality in responding to the existence of financial literacy. The first rationality certainly has an impact on his welfare in the future. The second rationality is of course aimed at values ​​that can be passed down to children.